Empowerment of Health Cadres in Utilizing Local Foodstuffs through Modisco Corn Processing to Increase Breast Milk Production for Postpartum Mothers - Agnes Isti Harjanti; Mudy Oktiningrum; Fransisca Glori (IJCS: International Journal of Community Service, 2022)
Nutrition status monitoring data in Indonesia in 2017 noted that the coverage of exclusive breastfeeding for babies up to the first 6 months only reached 35.7%. This is very low and still far from the coverage target set at 80%, which means that around 65% of babies do not get breast milk (ASI). In the Boja Health Center area, the coverage of exclusive breastfeeding is still low at 65%, while the target for the city of Semarang is 90%. From the description of the Puskesmas work area, the lowest breastfeeding coverage is in Meteseh Village. Exclusive breastfeeding coverage is still low at 45%. On average, postpartum mothers in Meteseh village don't think about additional nutritional intake to increase milk production, because they get little information or evidence on processing food ingredients that can be taken from local types of food. Health cadres don't know how to increase milk production for postpartum mothers, through providing additional food for making Modisco Corn. Modisco stands for Modified Dietetic Skim and Cotton Sheet Oil, which was discovered in 1973 by May White Head, according to White, the manufacture of Modisco is used to add nutrition to malnourished children, Modisco Corn is an additional modification given to facilitate breastfeeding and add nutrition to postpartum mothers. Processing Modisco Corn as a solution for postpartum mothers who breastfeed their babies, because corn fruit has the benefit of increasing milk production and is rich in nutrients. Modisco Corn is taught to Health Cadres, so that cadres have the ability to teach postpartum mothers at any time from generation to generation to increase the coverage of exclusive breastfeeding.